High Burden of Undernutrition among At-Risk Children in Neonatal Follow-Up Clinic in Rwanda - Theoneste Mutsindashyaka; Alphonse Nshimyiryo; Kathryn Beck; Catherine M. Kirk; Kim Wilson; Christine Mutaganzwa; Jessica D. Bradford; Silas Havugarurema; Vianney Bihibindi; Patient K. Ngamije; Joel M. Mubiligi; Ann C. Miller (Ubiquity Press, 2020)
Background: Sufficient knowledge of the disproportionate burden of undernutrition among vulnerable children is required for accelerating undernutrition reduction in low-income countries. Objectives: We aimed to assess the prevalence of stunting, underweight and wasting and associated factors among high-risk children born preterm, with low birth weight or other birth and neurodevelopmental injuries, who received nutritional support and clinical care follow-up in a Pediatric Development Clinic (PDC) in rural Rwanda. Methods: This cross-sectional study included all children from rural areas enrolled in PDC between April 2014-September 2017 aged 6-59 months at their last visit during this period. Anthropometric measurements, socioeconomic and clinical characteristics were extracted from an electronic medical records system. We used the World Health Organization child growth standards to classify stunting, underweight and wasting. Factors associated with undernutrition were identified using logistic regression analysis. Results: Of 641 children, 58.8% were stunted, 47.5% were underweight and 25.8% were wasted. Small for gestational age was associated with increased odds of stunting [OR 2.63; 95% CI 1.58-4.36] and underweight (OR 2.33; 95% CI 1.46-3.71), while history of feeding difficulties was significantly associated with wasting (OR: 3.36; 95% CI: 2.20-5.13) and underweight (OR: 2.68; 95% CI: 1.78-4.04). Later age at PDC enrollment was associated with increased odds of stunting (OR: 1.06; 95% CI: 1.01-1.11), underweight (OR: 1.09; 95% CI: 1.05-1.14) and wasting (OR: 1.07; 95% CI: 1.04-1.10). Conclusions: The prevalence of stunting, underweight and wasting are high in this at-risk population, highlighting the need for specific interventions to address undernutrition among children with similar characteristics. Early PDC enrollment of high-risk infants may reduce undernutrition risk.